Content analysis of forestry information reported in the environmental columns of two Nigerian newspapers (2016)
Despite availability and functioning of several newspapers in Nigeria, little or no change was observed in people’s attitude towards forestry related issues with attendant decline in the country’s forest resources. This paper reports the content analyses of forestry information reported by two prominent and national newspapers in Nigeria with the view to determining the frequency, space allotted, prominence and content categories of forestry related information in the newspapers from June 2009 to May 2014. Purposive sampling technique was used to select Guardian newspaper and Nigeria Tribune for the study. Data were collected from the editions on the days these newspapers have slot for environmental columns and were analysed using descriptive such as percentage and frequency as well as chi-square inferential statistics at α0.005. It was found that 76.9% of the environmental articles identified by the study were reported by Guardian while Nigerian Tribune reported 30.1%. Also, only 9.0% of the reported forestry related news were on the centre pages while 31.3% took up 201 –300 cm2 spaces of the newspapers under study. Climate change issues linked with forestry (CCLF) was the modal news category (26.9%) reported in the pages of the dailies under study. Further, a significant relationship was established between the newspapers and the space allotted, but none was observed between newspapers and prominence of forestry information as well as between the newspapers and categories of forestry information reported. Training of forestry information editors and canvassing for more sponsor of forestry information in Nigeria newspaper therefore becomes apt.